Legal Framework for Trademark Manifestation as Collateral Financing to Enhance the Capacity of MSMEs in Indonesia - Chairunnisa, Chairunnisa; Sudirman, Lu; Disemadi, Hari Sutra (Universitas Widya Gama Malang, 2024)
This article examines the manifestation of trademarks as collateral to enhance the capacity of Micro, Small, and Medium-sized Enterprises (MSMEs) in Indonesia. The study employs a normative research approach, drawing upon legal sources derived from legislation, relevant legal theories, and concepts. Data is analyzed using a qualitative juridical method and deductive reasoning. The research findings suggest that trademarks should be eligible as collateral since they meet the criteria of intangible movable property that can contribute to the growth and development of SMEs in Indonesia. However, the practical application of trademarks as collateral is hindered by existing regulations and the absence of a specialized intellectual property asset appraisal institution. Such measures are crucial in fostering MSMEs and, ultimately, improving the welfare of the Indonesian society.